Trial registries for transparency and accountability in clinical research - De Vito, NJ (2022)
Background: Over the past 30 years clinical trial registries have become a key institution aiming to reduce bias and waste within global clinical research. Funders, journals, and governments have made prospective trial registration a near universal requirement and a route for results dissemination. This thesis examines the use of registries within the current research landscape and examines how they function as tools for aiding and informing research.